A rare cause of cyanosis: Congenital methemoglobinemia. Issue 7 (10th July 2021) - Guedri, Rahma; Missaoui, Nada; Essaddam, Leila; Ben Becher, Saayda
Abstract: Congenital Methemoglobinemia is a rare condition that may mimic congenital heart diseases. There are two types of congenital Methemoglobinemia. The type I is usually benign. The enzyme deficiency is limited to red blood cells. Clinically, the patient presents cyanosis without neurological disorders. Whereas, in type II, cyanosis is associated with severe neurological impairment. Abstract : Congenital Methemoglobinemia is a rare condition that may mimic congenital heart diseases. There are two types of congenital Methemoglobinemia. The type I is usually benign. The enzyme deficiency is limited to red blood cells. Clinically, the patient presents cyanosis without neurological disorders. Whereas, in type II, cyanosis is associated with severe neurological impairment